Reducing readmissions and improving patient experience following urological surgery, through early telephone follow-up. Issue 2 (16th April 2020) - Nettleton, Jeremy; Jelski, Joseph; Ahmad, Adnan
Abstract : Readmission from urological surgery is common, with a readmission rate for day case surgery of 3.7% and 26% for robot-assisted cystectomy. Readmission to secondary care and representation to primary care are both expensive and preventable. This project aimed to reduce both and also enhance the care of patients following urological surgery in a large tertiary referral centre, within the National Health Service. A retrospective telephone follow-up (TFU) survey was set up in the early postoperatively period to measure reattendance and readmission rates and perception of care received. Patients were also asked to suggest how improvement could be made. Quality improvement tools were used to optimise and review the methods and timing of TFU. TFU was initiated as a strategy to enhance care and reduce readmission rates. Phone calls were targeted to occur between 48 and 72 hours following discharge. During the intervention period, 484 phone calls were attempted with 343 being successful. Reattendance rates were reduced by 13% and patient satisfaction improved by 19.6%, following TFU. This intervention also generated additional income for the organisation and enhanced patient satisfaction in the early postoperative period.